The Role of Character Education in Building Noble Morals in Madrasah Tsanawiyah: (A Case Study of Implementation in Grade VIII at MTs Darul Hadist Hutabaringin, Mandailing Natal Regency) - Purnama, Elida; Marwah, Marwah; Pahutar, Elisah; Wijaya Parinduri, Handi; Noprianti, Noprianti (ALACRITY : Journal of Education, 2024)
This study aims to explore the implementation of character education in building noble morals among Grade VIII students at MTs Darul Hadist Hutabaringin in Mandailing Natal Regency. The research adopts a qualitative approach using a case study method, where data is collected through observation, in-depth interviews, and documentation. The research subjects include students, teachers, the head of the madrasah, and parents. The findings reveal that character education at MTs Darul Hadist Hutabaringin is integrated into daily learning through teacher role models, extracurricular activities such as scouting and spiritual studies, and parental involvement in supporting school programs. Teachers play a significant role in instilling moral values, while extracurricular activities provide a space for students to practice these values outside the classroom. The study also identifies challenges, such as external environmental influences, particularly social media, which may hinder students’ internalization of character values. Additionally, limitations in time and resources pose obstacles to the optimal implementation of character education. The study concludes by emphasizing the importance of stronger collaboration between schools, parents, and the community to reinforce character education. Continuous evaluation and innovation are also necessary to address technological challenges, ensuring character education remains relevant and effective in shaping a morally upright generation.